Efficacy study of galantamine in possible Alzheimer's disease with or without cerebrovascular disease and vascular dementia in Thai patients: A slow-titration regimen - Nantika Thavichachart (2018)
The objective is to evaluate the efficacy of galantamine when a slow titration regimen is employed in Thai Alzheimer's disease (AD) patients with or without cerebrovascular disease and vascular dementia (VaD). A 6-month, multicentre, open-label, uncontrolled trial was undertaken in 75 AD patients. Eligible patients received an initial galantamine dose of 8 mg/day and escalated over 5-8 weeks to maintenance doses of 16 or 4mg/day. Primary efficacy measures were AD Assessment Scale-cognitive subscale (ADAS-cog) and the Clinician's Interview-Based Impression of Change-Plus version (CIBIC-plus). The Behavioural Pathology in AD Rating Scale (BEHAVE AD), the AD Cooperative Study Activities of Daily Living Inventory and Pittsburgh Sleep Quality Index were the secondary efficacy variables. Analyses were based on the intent-to-treat population. Treatment with galantamine showed significant improvement in cognition on the ADAS-cog and CIBIC-plus at month 6. Galantamine showed favourable effects on activities of daily living. Behavioural symptoms and sleep quality were also significantly improved (p < 0.05). Galantamine was well tolerated. The adverse events were mild-to-moderate intensity. The most frequent adverse events commonly reported were nausea (16.4%), dizziness (9.6%) and vomiting (6.8%). The results of this study may be consistent with galantamine being an effective and safe treatment for mild-to-moderate AD patients with or without cerebrovascular disease and VaD. Flexible dose escalation of galantamine was well tolerated. The daily maintenance dose of galantamine was 16 mg/day, followed by a back up dose of 24 mg/day. © Blackwell Publishing Ltd, 2006.